2002
DOI: 10.1016/s1540-7489(02)80350-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial reaction steps in the condensed-phase decomposition of propellants

Abstract: Word count: 5420 = 3250 words + 420 (eqn) + 350 (ref) + 1 table (400) + 5 figures (1 000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…The major ions cited are m/z 14, 15, 16, 17, 18, 27, 28, 29, 30, 31, 43, 44, 45 and 46, which are all seen in our experiment except for m/z 14, 17 and 18. We are currently continuing our studies in developing a mechanism and its comparison with theoretical work by Melius and colleagues which suggests possible condensed‐phase initial reaction steps in nitrate ester decomposition 37. The reaction pathway shows consistencies with our findings, and will be more fully addressed in a future publication.…”
Section: Resultssupporting
confidence: 69%
“…The major ions cited are m/z 14, 15, 16, 17, 18, 27, 28, 29, 30, 31, 43, 44, 45 and 46, which are all seen in our experiment except for m/z 14, 17 and 18. We are currently continuing our studies in developing a mechanism and its comparison with theoretical work by Melius and colleagues which suggests possible condensed‐phase initial reaction steps in nitrate ester decomposition 37. The reaction pathway shows consistencies with our findings, and will be more fully addressed in a future publication.…”
Section: Resultssupporting
confidence: 69%
“…From 2012 to 2014, we conducted thermal studies of NP aging over two years in headspaces containing air, nitrogen, or water to study how that headspace composition impacts the reaction pathway of the NP degradation. Those studies experimentally confirmed the mechanisms of NP degradation proposed by several research groups [33][34][35]39]. It is known that the very first step in NP degradation is HONO formation, which then decomposes into NOx, water, or HNOx depending on the temperature and headspace condition.…”
Section: Part Two: Np Thermal Stability In a Confined Systemsupporting
confidence: 76%
“…The stability of various classes of polynitro compounds has been investigated previously. However, relatively few studies have focused on understanding the decomposition pathways of BDNPA/F at temperatures below 70°C [12,18,19,[22][23][24][25][26]. Also, although numerous studies have focused on the aging behavior of the PBX9501 [12,13,16,[27][28][29][30][31][32], few have focused on the NP alone.…”
Section: Part Two: Np Thermal Stability In a Confined Systemmentioning
confidence: 99%
“…This is consistent with earlier findings for the decomposition of methylnitramine, a prototype material of nitramines. 7,14 An extension of the equatorial NÀNO 2 bond also leads to the bond breaking. However, due to a small attraction between the C 4 H 8 N 7 O 6 radical and the NO 2 , the structural relaxation causes the NO 2 to rebind with the rest of the molecule.…”
Section: Decomposition Mechanismsmentioning
confidence: 99%